Halal Quality Management System: A comparison between Halal and Kosher - Adam, Abdul Rahman; Bahari, Che Amnah; Abdul Jalil, Mohd. Noh (2020)
This study discusses Halal and Kosher Food. How are these different dietary systems managed by food establishments? The management of halal food has been studied from different perspectives. Management of Halal food issues in Singapore adopts the 10 principles of Halal Quality Certification Strategic Unit. However, no attempt has been made to systematically review the published literature on Halal and Kosher food system management. It has been an industry practice for caterers to apply Halal Certification even while they operate Non Halal Kitchens. It is very challenging for caterers to maintain the Halal Certification. The objective of Halal Quality Management system is to guide the Halal Certificate Holders in maintaining their Halal status. The principles developed contain very detailed to ensure that Halal integrity and trace ability are maintained as well as no religious breaches. The Muslim worker in the company plays a very important role in ensuring that this system is followed. Thus, this reminds the Non-Muslims to be very serious whenever they are involved in producing Halal Food to the Muslim community